Koinōnia and the Psychology of Possession - Konrádová, Veronika (2022)
This paper addresses the concept of koinōnia discussed in Plato’s Republic. It focuses on the specific ways the term enters the discussion about social organisation within the guardian class, such as the proposal for abolishing a nuclear family in favour of the community of wives and children. The paper aims to reveal the psychological basis connecting Plato’s socio-economic proposals to his principal ethical and political concerns. It examines (i) the argument supporting the proposals of the social organisation of the guardians, (ii) the psychological background of these proposals, (iii) the socio-cultural context against which these proposals are defined and (iv) the position of these considerations in the broader scheme of Plato’s thought.